Hands-On Contextual Learning Experimentation on Psychomotor Abilities - Billyardi Ramdhan (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2020)
The purpose of this study was to determine the effect of contextual learning models based on hands-on activities on students' psychomotor abilities. This type of research is a quasi-experimental using pretest posttest control group design. The results showed the psychomotor ability of students in the experimental class averaged 79.63 which was categorized as